Best Practices in near-miss reporting - Erdoğan, Ilknur (My University, 2012)
The ISM Code requires that hazardous situations are to be reported to the company, investigated and analysed in order to prevent future happenings. Near-miss reporting gains importance in this respect, because, near-misses are believed to represent experiences and mistakes that should be shared to learn from in order to prevent bigger accidents. However, the general belief is that near-misses are not reported at the level as expected by the authorities. Some studies have been carried out to find out main barriers to reporting. The main objective of this study is to find out some best practices about near-miss reporting from the companies that are active in Swedish and Finnish shipping industry and believed to have high level of safety understanding within their organization. In addition, external reporting systems such as Insjö and newly developing ForeSea have been investigated in this study. The study is based on interviews with a total of 32 representatives, both shore-based and ship-based, from four different companies. Also, one representative from Insjö has been interviewed. It is found out that the representatives from these companies claim to have progressed in achieving 'No-blame culture' within their organization. Besides, they have achieved to put a reporting system in use and try to make it work as good as possible. The representatives claim that they are interested in having a more international reporting system where they can share experiences. The providers of such systems try to improve their systems. However, the actual current benefit of a such system is unclear. The majority of the participants believe that near-miss reporting in principle has a significant effect creating and enhancing the safety culture. However, the actual benefits of the near-miss reporting are reported as being limited. Further, it seems that the companies are not yet utilizing the reported data for establishing trends to improve the follow-up and the awareness within the organization.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering